Transportation engineering : planing and design - Wright, Paul H.; Ashford, Norman J.; Stammer, Robert J. (New York : John Wiley and Sons, 1998)
This book is about: Introduction to transportation systems; Operation and control of transportation vehicles; Transportation planning; Design of land transportation facilities; Design of air transportation facilities; Design of water transportation facilities.
Keywords: Transportation engineering; Transportation engineering; Civil engineering